2008
DOI: 10.3346/jkms.2008.23.4.598
|View full text |Cite
|
Sign up to set email alerts
|

Single Institutional Experience of Bladder-Preserving Trimodality Treatment for Muscle-Invasive Bladder Cancer

Abstract: The authors designed this study to determine the clinical effectiveness of trimodality treatment, i.e., transurethral resection of a bladder tumor (TURBT) and concurrent chemoradiotherapy (CRT). Twenty patients with a muscle-invasive bladder cancer were treated by TURBT followed by concurrent cisplatin (75 mg/m 2 day), administered on weeks 1 and 4 of radiotherapy. According to residual tumor status after TURBT, patients were classified into patients with a complete TURBT group and incomplete TURBT group. Resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Thus, several studies were done to identify the predictors for ideal candidates for tri-modality treatment. Similar to previous studies [13][14][15]18,21,24,33,43,44], our study showed that completeness of TUR, PS, response to induction treatment and TNM stage were the main factors affecting survival. However, multivariate analysis showed that TNM staging was the main survival predictor.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, several studies were done to identify the predictors for ideal candidates for tri-modality treatment. Similar to previous studies [13][14][15]18,21,24,33,43,44], our study showed that completeness of TUR, PS, response to induction treatment and TNM stage were the main factors affecting survival. However, multivariate analysis showed that TNM staging was the main survival predictor.…”
Section: Discussionsupporting
confidence: 90%
“…The optimum combination of chemotherapeutic drugs needs to be identified not only to improve efficacy but also to minimize toxic effects related to treatment [9]. In our study the rate of CR in group I and II was 80% and 86.7% respectively which is comparable to previous studies [15][16][17][18][19][20][21][22][23][24], while, other studies showed lower CR rate and this is explained by that the majority of our patients were T2. [9,[25][26][27][28][29][30][31].…”
Section: Discussionsupporting
confidence: 83%
“…From the literature we identified 17 studies that discussed the management of patients who had a complete response to CRT. A summary of the 17 studies [2–18] is shown in Tables 1 and 2. Table 1 shows the response and local recurrence rates after bladder conservation therapy and Table 2 shows the management and outcomes of local recurrences after bladder conservation therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Patients were deliberately selected for RCT with favourable disease factors; 92% of patients appeared to have cT2 disease, and only 10% Tis TCC [34]. Similar results were seen in a smaller study of 20 patients from Korea published in 2008 combining 45-65 Gy radiotherapy with concurrent cisplatin [35].…”
Section: Muscle Invasive Bladder Cancer: Multimodality Therapy With Rmentioning
confidence: 64%